The Effect of Protein Induction of Brachionus sp. Toward In-Vivo Response of Cluster Differentiation-8 (CD8) Cantang Grouper (Epinephelus sp.) Infected by VNN (Viral Nervous Necrosis) - Martiningsih, Nur Fauziyah; Yanuhar, Uun; Musa, Mohammad; Kumalaningrum, Dwi Retna (Jurnal Penelitian Pendidikan IPA, 2023)
The large demand for grouper conduce increase production intensively in various ways, by increasing the production of grouper aquaculture raises causing new problems, one of which is infection with VNN disease. The use of antibiotics to treat VNN infections is prohibited or no longer recommended by the government. An alternative way to deal with VNN infection is by increasing the body's immunity in the fish itself. One effort that can be done to increase the body's immunity in grouper is by administering Brachionus sp. protein extracts. This research was conducted to determine whether the Brachionus sp. has an effect on the immune system in cantang grouper (Epinephelus sp.) as indicated by the emergence of Cluster Differentiation-8 (CD8) expression in fish that have been infected with VNN. The proteins contained in Brachionus sp. that has three type molecular weight (122.73 kDa, 75.49 kDa, and 13.77 kDa) potential as an ingredient for treating VNN-infected fish. It is hoped that this can improve the immune system in Epinephelus sp. infected with VNN. Protein Brachionus sp. given by injection at a dose of 35 µl, 105 µl and 170 µl per 150 gr Epinephelus sp. 105 µl was the best concentration in boosting the immune system in the tested Epinephelus sp., as indicated by a decreased CD8 count.